Toll-like receptors in the immature human brain. (18th April 2012) - Supramaniam, V; Vontell, R; Patkee, P; Wyatt-Ashmead, J; Hagberg, H; Rutherford, M
Abstract : Toll-like receptors (TLR), found on glial and neuronal cells, are major components of the innate immune system. They act as sensors that recognise pathogen-associated or damage-associate molecular patterns. There is limited information on these receptors in the immature brain. Generally TLR-2 is triggered via gram-positive bacterial infections, however, recent research in animal models have found that TLR2 plays an important role in brain injury following hypoxic-ischaemia (HI)1 and TLR3 activation further enhances HI-induced brain injury2, whilst LPS-induced (gram negative) oligodendrocyte injury was shown to be mediated by TLR4 activation.3 We used immunohistochemistry and in situ hybridisation to investigate TLR2, 3 and 4 expression in the immature human brain. Post-mortem neonatal cases (22-39wk GA) were recruited with parental consent and ethics approval. The preterm study cohort consisted of cases without overt brain pathology on post-mortem MRI and conventional autopsy (control), cases with evidence of germinal matrix/intraventricular haemorrhage (GMH/IVH), periventricular leukomalacia (PVL), suspected ascending amniotic fluid infection and term hypoxic-ischaemic encephalopathy (HIE). Immunohistochemistry results showed that control brains had mainly TLR4 expression, whilst the most prominent expression of TLR2, 3 and 4 was seen in PVL cases. Of interest is the activation of all three TLRs in the infection cases, even in the absence of overt injury to the brain on MRI. GMH/IVH and HIE cases showed predominantly TLR3 expression. The validity of the protein expression was confirmed using in situ hybridisation. We have demonstrated, for the first time, the expression of TLRs in the immature human brain with and without pathology.